2016
DOI: 10.1021/acscombsci.6b00046
|View full text |Cite
|
Sign up to set email alerts
|

Three-Component, Diastereoselective Prins–Ritter Reaction for cis-Fused 4-Amidotetrahydropyrans toward a Precursor for Possible Neuronal Receptor Ligands

Abstract: Here, we report an unprecedented, highly diastereoselective Prins-Ritter reaction of aldehydes, homoallylic alcohols, and nitriles in a three-component coupling reaction for the synthesis of tetra-cis-substituted 4-amidotetrahydropyrans. In this study, the reaction was not only applied for carbohydrate-based heterobicycles but also for more complex heterotricycles, showing acceptable levels of conversion yield (42-97% BRSM) and exclusive diastereoselectivity. Furthermore, the latter heterotricycles were conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Finally, the hydrolytic removal of the menthyl, methyl, and TFA groups was attempted towards both enantiomers of TKM-38, 3 and 3* (Scheme 6). A preliminary study with 21* (2S) showed the low reactivity under acidic conditions (6 M aq HCl, MeOH, 65 °C) [5,24], which resulted in the quantitative recovery of the substrate 21* (2S). We then examined an alkaline hydrolysis (KOH, MeOH, H 2 O, 40 °C) [25,26], which gratifyingly furnished (2S)-TKM-38 (3*) in a good yield (77%) after ion-exchange chromatography (Dowex ® 50W x8-200, H + form).…”
Section: Enantiospecific Synthesis Of Tkm-38mentioning
confidence: 99%
“…Finally, the hydrolytic removal of the menthyl, methyl, and TFA groups was attempted towards both enantiomers of TKM-38, 3 and 3* (Scheme 6). A preliminary study with 21* (2S) showed the low reactivity under acidic conditions (6 M aq HCl, MeOH, 65 °C) [5,24], which resulted in the quantitative recovery of the substrate 21* (2S). We then examined an alkaline hydrolysis (KOH, MeOH, H 2 O, 40 °C) [25,26], which gratifyingly furnished (2S)-TKM-38 (3*) in a good yield (77%) after ion-exchange chromatography (Dowex ® 50W x8-200, H + form).…”
Section: Enantiospecific Synthesis Of Tkm-38mentioning
confidence: 99%
“…An interesting three‐component Prins‐Ritter reaction of lactone 1 with benzaldehyde, acrolein or cinnamaldehyde and acetonitrile or benzonitrile to obtain 4‐amidotetrahydropyrans 94a‐f diastereoselectively was disclosed by Oikawa and co‐workers (Scheme ). [51a] The Prins‐Ritter reaction of the lactone 1 was further extended to the reaction with 1,3,5‐trioxane in presence of AlCl 3 , p TsOH or MsOH to deliver the Cl, OTs or OMs substituted tetrahydropyrans 95a‐c in moderate yields. [51b]…”
Section: Other Applications Of Lactonementioning
confidence: 99%
“…[51a] The Prins‐Ritter reaction of the lactone 1 was further extended to the reaction with 1,3,5‐trioxane in presence of AlCl 3 , p TsOH or MsOH to deliver the Cl, OTs or OMs substituted tetrahydropyrans 95a‐c in moderate yields. [51b]…”
Section: Other Applications Of Lactonementioning
confidence: 99%
“…Finally, hydrolytic removal of menthyl, methyl, and TFA groups were attempted toward both enantiomers of TKM-38 (3/3*, Scheme 6). Preliminary study with 21* (2S) showed the low reactivity under acidic conditions (6 M aq HCl, MeOH, 65 °C) [5,21], which resulted in quantitative recovery of the substrate 21* (2S). We then examined alkaline hydrolysis (KOH, MeOH, H2O, 40 °C) [22,23]…”
Section: Enantiospecific Synthesis Of Tkm-38mentioning
confidence: 99%